Identification of an Arabidopsis solute carrier critical for intracellular transport and inter-organ allocation of molybdate - Gasber, A.; Klaumann, S.; Trentmann, O.; Trampczynska, A.; Clemens, Stephan; Schneider, Sabine; Sauer, Norbert; Feifer, I.; Bittner, F.; Mendel, R. R.; Neuhaus, H. E. (Plant Biology, 2011)
Plants represent an important source of molybdenum in the human diet. Recently, MOT1 has been identified as a transport protein responsible for molybdate import in Arabidopsis thaliana L.; however, the function of the homologous protein MOT2 has not been resolved. Interestingly, MOT2-GFP analysis indicated a vacuolar location of this carrier protein. By site directed mutagenesis at the N-terminal end of MOT2, we identified a di-leucine motif that is essential for driving the protein into the vacuolar membrane. Molybdate quantification in isolated vacuoles showed that this organelle serves as an important molybdate store in Arabidopsis cells. When grown on soil, leaves from mot2 T-DNA mutants contained more molybdate, whereas mot2 seeds contained significantly less molybdate than corresponding wild-type (Wt) tissues. Remarkably, MOT2 mRNA accumulates in senescing leaves and mot2 leaves from plants that had finished their life cycle had 15-fold higher molybdate levels than Wt leaves. Reintroduction of the endogenous MOT2 gene led to a Wt molybdate phenotype. Thus, mot2 mutants exhibit impaired inter-organ molybdate allocation. As total concentrations of the molybdenum cofactor (Moco) and its precursor MPT correlates with leaf molybdate levels, we present novel evidence for an adjustment of Moco biosynthesis in response to cellular MoO levels. We conclude that MOT2 is important for vacuolar molybdate export, an N-terminal di-leucine motif is critical for correct subcellular localisation of MOT2 and activity of this carrier is required for accumulation of molybdate in Arabidopsis seeds. MOT2 is a novel element in inter-organ translocation of an essential metal ion. © 2011 German Botanical Society and The Royal Botanical Society of the Netherlands.
Keywords: Micronutrient; Molybdate; Solute carrier; Transport; Vacuole